Sensação térmica urbana em área residencial planejada no município de Santarém-Pará, Amazônia, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The objective of this research was to evaluate the microclimatic variables, perception and urban thermal sensation of residents of a residential area planned for low income families in the city of Santarém-Pará. It was collected from data of temperature, relative air humidity and wind speed, in addition to pre-set application applications. The experiment occurred on August 15, 2018, in a transect with seven points in the residential. Forms were applied in internal area (houses) and external in the total of 115 forms, for a population aged 15 to 60 years. With the microclimatic information of the place were calculated the Temperature and Humidity, Temperature and Humidity modified and Temperature Effective as a function of the Wind, which were correlated with the subjective sensations of the local population. The results indicate that the Effective Temperature index as a function of the Wind was the most compatible with the sensation and the personal perception of the interviewees. It was very evident the thermal discomfort felt by the population, between the period of 12 to 15 h in the external area and 15 to 18 h in the internal area (houses). The brightness temperature in the residential trim cutout there is a gradual increase in temperature from 27 to 30 ° C along the transect, compared to a forward occupancy area, it is possible to check the highest temperature at 33 ° C.
Keywords: Conforto Térmico; Área planejada; Clima Urbano; CNPQ:: Ciências Biológicas; Climatologia Ambiental